A STUDY OF CODE-SWITCHING USED BY AN ENGLISH TEACHER IN TEENAGERS’ EFL CLASS - Gloria Hede; Josefa J. Mardijono (Institute of Research and Community Outreach - Petra Christian University, 2015)
This study is aimed to analyze the types of code-switching used by the teacher and under what circumstances the switching occur to identify its function. Using qualitative approach, the writer did this study based on code-switching theory of Wardhaugh (2006) and classroom interaction of Walsh (2011). The findings revealed that the teacher used both types of code-switching, intra-sentential and inter-sentential switching. The function of the code-switching identified through the four features of classroom interaction were control of interaction to control the participation, content, procedure of the lesson; speech modification to clarify meaning, to ensure the students’ understanding; elicitation technique to elicit response for checking comprehension; repair to correct error directly or get the students to correct the errors. From this study, it could be concluded that the teacher used code-switching to make the learning process clearer, so the students would not get confused and would not have misunderstanding in the classroom.